Malignant transformation of oral proliferative verrucous leukoplakia: A systematic review and meta‐analysis. (19th May 2021) - Ramos‐García, Pablo; González‐Moles, Miguel Ángel; Mello, Fernanda Weber; Bagan, Jose V.; Warnakulasuriya, Saman
Abstract: Objectives: To investigate the available evidence on the malignant transformation (MT) of oral proliferative verrucous leukoplakia (PVL). Material and Methods: We searched six main electronic and three grey literature databases in a two‐phase process. Cohort studies investigating MT of PVL were eligible for inclusion. The risk of bias (RoB) was assessed using a specific tool developed by the Joanna Briggs Institute. Proportion meta‐analyses were performed using a random‐effects model. Results: Study selection resulted in the inclusion of 17 studies. The pooled proportion of MT was 43.87% (95% CI = 31.93–56.13). Females (64.02%, 95% CI = 54.87–72.75) were more affected by PVL than males (35.98%, 95% CI = 27.25–45.13). Gingiva (39.6%) and buccal mucosa (21.6%) were the most frequent PVL sites. No conclusive results were found between MT and sex or age distribution, tobacco, or alcohol consumption. Gingiva was the most common site for MT (39.9%), and the most frequent histopathological subtype was conventional squamous cell carcinoma (62.1%). Four studies were classified as low, nine as moderate, and four as high RoB. Conclusion: The MT pooled proportion was 43.87%. Among OPMDs, PVL has the highest risk to transform to malignancy. Development and agreement on diagnostic criteria for PVL would reduce the heterogeneity among future studies.